EXPECTATION AND REWARD IN DEMENTIA: THE CASE OF MUSIC. Issue 12 (15th November 2016) - Clark, Camilla; Golden, Hannah; McCallion, Oliver; Nicholas, Jennifer; Cohen, Miriam; Mummery, Catherine; Schott, Jonathan; Warren, Jason
Abstract : Music is a universal stimulus that generates powerful emotion and reward. Responses to music depend on internalised 'rules' that generate strong psychological expectancies and have been little studied in disease. We assessed expectations generated while listening to music and associated affective responses in cohorts of patients with Alzheimer's disease (AD) and frontotemporal lobar degeneration (behavioural variant frontotemporal dementia (bvFTD), semantic dementia (SD) and progressive nonfluent aphasia (PNFA) in relation to healthy older individuals. We created a set of short novel melodies in which cadence was manipulated such that the melodies sounded either 'finished' or 'unfinished'. Participants were asked to label each melody explicitly and to rate how pleasing they found the ending. Relative to the healthy control group, AD and bvFTD showed a significant deficit of labelling of melodies as finished or unfinished. All participants, apart from the SD group, found unfinished melodies significantly more unpleasant than finished melodies. In VBM, grey matter correlates of melody classification accuracy and pleasantness rating were identified in a distributed network including anterior temporal, medial and lateral orbitofrontal cortices. Music is a promising tool with which to probe the differential effects of dementia diseases on reward and rule–based processes.